Study of aerosol hygroscopic events over the Cabauw experimental site for atmospheric research (CESAR) using the multi-wavelength Raman lidar Caeli. (November 2015) - Fernández, A.J.; Apituley, A.; Veselovskii, I.; Suvorina, A.; Henzing, J.; Pujadas, M.; Artíñano, B.
Abstract: This article presents a study of aerosol optical and microphysical properties under different relative humidity (RH) but well mixed layer conditions using optical and microphysical aerosol properties from multi-wavelength (MW) Raman lidar and in-situ aerosol observations collected at the Cabauw Experimental Site for Atmospheric Research (CESAR). Two hygroscopic events are described through 3 backscatter ( β ) and 2 extinction ( α ) coefficients which in turn provide intensive parameters such as the backscatter-related Ångström exponent (å β ) and the lidar ratio ( LR ). Along with it, profiles of RH were inferred from Raman lidar observations and therefore, as a result of varying humidity conditions, a shift on the aerosol optical properties can be described. Thus, it is observed that as RH increases, aerosols uptake water vapour, augment their size and consequently the å β diminishes whereas the LR increases. The enhancement factor based on the backscatter coefficient at 532 nm, which characterizes the aerosol from hygroscopic standpoint, is also estimated. Finally, microphysical properties that are necessary for aerosol radiative forcing estimates – such as volume, effective radii, refractive index and size distribution, all vertically resolved – are retrieved using the inversion with regularization. Using this method, two hygroscopic events are described in detail. Highlights: As relative humidity increased the å β decreased and lidar ratio increased. Aerosol size increased and ref. index decreased at high RH. The enhancement factor curve suggested possible deliquescence processes. This behavior is attributed to organic matter and marine aerosols.